Boundary blow-up rate and uniqueness of the large solution for an elliptic cooperative system of logistic type. (February 2017) - López-Gómez, Julián; Maire, Luis
Abstract: This paper ascertains the blow-up rates of each of the components of a singular boundary value problem related to a cooperative system of logistic type, in order to establish the uniqueness of the large solution. Astonishingly, the cooperative coupling does not change the blow-up rates of the uncoupled system provided these blow-up rates are sufficiently close, though it changes exactly one of them, keeping invariant the other, when they are bounded away. This seems to be the first time where this change of behavior has been documented in the literature.